Impact of Serum Retinol-Binding Protein 4 Levels on Regulation of Remnant-Like Particles Triglyceride in Type 2 Diabetes Mellitus. (19th March 2013) - Yamaaki, Naoto; Yagi, Kunimasa; Kobayashi, Junji; Nohara, Atsushi; Ito, Naoko; Asano, Akimichi; Nakano, Kaoru; Liu, Jianhui; Okamoto, Takuya; Mori, Yukiko; Ohbatake, Azusa; Okazaki, Satoko; et al.
Abstract : Background . Although retinol-binding protein 4 (RBP4) associates with insulin resistance and remnant-like particles triglyceride (RLP-TG) elevated in the insulin resistant state, few data exist regarding the relationship between RBP4 and RLP-TG. Subjects and Methods . The study included 92 Japanese type 2 diabetic mellitus (T2DM) male patients (age 60.5 ± 13.6 years, body mass index (BMI) 24.7 ± 4.1  kg/m 2, waist circumference (WC) 88.4 ± 10.7  cm, and HbA1c (NGSP) 7.2 ± 1.9 %). Patients on medications affecting insulin sensitivity, including fibrates, biguanides, and thiazolidinedione, were excluded. Visceral fat area (VFA) and subcutaneous fat area (SFA) were measured by computed tomography. Results . RBP4 levels showed a significant positive correlation with RLP-TG (r = 0.2544 and P = 0.0056 ), TG (r = 0.1852 and P = 0.041 ), RLP-TG/TG (r = 0.23765 and P = 0.0241 ), and age (r = − 0.2082 and P = 0.0219 ), although there was no significant correlation with VFA, SFA, adiponectin levels, or homeostasis model of assessment insulin resistance (HOMA-R). Multiple regression analysis revealed that RBP4 was an independent determinant of RLP-TG (P = 0.0193 ) but was not a determinant of TG. Conclusions . RBP4 correlates positively with serum RLP-TG independent of fat accumulation in T2DM. RBP4 may regulate remnant metabolism independent of glycemic control in T2DM.